KECEMASAN SISWA SEKOLAH MENENGAH ATAS SAAT PEMBELAJARAN DARING DI TENGAH PANDEMI COVID-19 - Mohammad Muhyidin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2022)
Abstract: In March 2020 the Indonesian government imposed online learning from home for all school students as a social restriction effort during the COVID-19 pandemic. This study aims to determine the anxiety experienced by students and their efforts to overcome this anxiety. Ten informants from high school students were included in this study. They were given a questionnaire form containing open-ended questions related to the topic of this research. Data from filling out the questionnaire showed that there was students’ anxiety when learning online from home which included difficulties in understanding the material, difficulties in carrying out assignments, problems with the internet network, technical problems, and a sense of worry about the next task. In overcoming this anxiety, they do things like the following, namely studying independently, every time doing a task immediately, discussing with teachers and friends, encouraging themselves, also carrying out other activities, among others, watching movies, listening to music, eating and exercising. Keywords​: ​​ Anxiety, Online Learning, Covid-19